Spirometric evaluation of pulmonary function in Yazd’s dental laboratory workers in 1398 - Hatami, M; Mehrpaevar, AH; Kouchak zadeh, A (Faṣlnāmah-i ʻilmī-i takhaṣṣuṣī-i ṭibb-i kār, 2020)
Introduction: Spirometry is used as a screening method for occupational lung diseases. Dental laboratory workers are exposed to solvent vapors, toxic gases, and dust from metal alloys, acrylics, and gypsum. This study aimed to investigate the spirometric function of lung function in dental staff in Yazd. Materials and Methods: This descriptive cross-sectional study was performed on 37 technicians of dental laboratories in Yazd in the three months of spring 2017. To evaluate respiratory problems and their pulmonary function, standard respiratory and spirometry questionnaires according to ATS / ESR guidelines were used, respectively. Data were analyzed by SPSS software version 18 using Mann-Whitney U, Chi-square, and Student's T-test. Results: Mean age of participants was 35.59±1.13. 54% of participants had no respiratory symptoms. The most common respiratory complain were dry and exudative cough. The work field was the only influential factor in FVC%. Age and work experience, and exercise no significant effect on respiratory parameters. Overall spirometry parameters were in the normal pattern range, and only 5% of participants showed a mild restrictive pattern. Conclusion: Spirometric pulmonary function of Yazd'dental laboratory technicians was in the normal range, and possibly working in the dental laboratory did not have a significant effect on the pulmonary Function of technicians based on spirometric indices.